NaOH/clinoptilolite-Fe3O4 as a novel magnetic catalyst for producing biodiesel from Amygdalus scoparia oil: Optimization and kinetic study. (1st November 2021) - Joorasty, Mahsa; Hemmati, Alireza; Rahbar-Kelishami, Ahmad
Highlights: This study aims at synthesizing NaOH/Clinoptilolite-Fe3 O4 as a novel magnetic alkali catalyst for biodiesel production. The characterization of catalyst was investigated by XRD, FTIR, FESEM, EDX, and VSM analyses. The RSM-CCD approach was used to optimize biodiesel production from Amygdalus scoparia oil. The highest biodiesel yield was 91% under optimum reaction condition. The magnetic catalyst was recovered four times with a low loss in the catalytic activity. Abstract: This study aims at synthesizing NaOH/Clinoptilolite-Fe3 O4 as a novel magnetic alkali catalyst to use for the transesterification reaction of Amygdalus scoparia oil. Clinoptilolite is a highly porous natural zeolite with a high specific surface area that can increase physical contact between catalyst surface and oil molecules. After synthesis, NaOH/Clinoptilolite-Fe3 O4 were characterized by XRD, FTIR, FESEM, EDX, BET, TPD-CO2, and VSM analyses. Then, the synthesized catalyst was utilized to produce biodiesel through the electrolysis method. The impact of significant factors, including catalyst weight (0.3–0.9 wt%), time (2.5–6 h), and methanol to oil (6:1–12:1), were investigated using response surface methodology based on the central composite design (RSM-CCD). The highest biodiesel yield was achieved under the optimum conditions of methanol to oil molar ratio of 10.43:1, catalyst weight of 0.5 wt%, and reacting time of 2.5 h. The RSM-CCD model could estimate biodiesel yield with a high regression coefficient (R 2 ) value of 0.9982 and an adjusted coefficient of determination (adj-R 2 ) of 0.9966. The catalyst was recycled five times with an average biodiesel yield of 86.8%. The activation energy obtained from the kinetic study was 9.21 kJ.mol −1 . The physicochemical properties of biodiesel produced from Amygdalus scoparia oil under the optimal conditions were within limits determined by the ASTM standard.